Descartes' Meditations : background source materials - Ariew, Roger; Cottingham, John, 1943-; Sorell, Tom (1998)
"No single text has more importance for the history of philosophy than Descartes' Meditations. This unique collection of background material has been translated from the original French and Latin. The texts gathered here illustrate the kinds of principles, assumptions, and philosophical methods that were commonplace when Descartes was developing his ideas."--Jacket
Dialectic / Petrus Ramus -- That nothing is known / Francisco Sanches -- The promotion of mathematics / Christopher Clavius -- Metaphysical disputations / Francisco Suarez -- Wisdom / Pierre Charron -- A compendium of philosophy in four parts / Eustachius a Sancto Paulo -- Corpus of philosophy / Scipion Dupleix -- The use of reason, The impiety of the deists, and The truth of the sciences / Marin Mersenne -- Unorthodox essays against the Aristotelians / Pierre Gassendi -- The two truths and The immortality of the soul / Jean de Silhon -- Dialogue on the diversity of religions and Little skeptical treatise / Francois de la Mothe Vayer -- Universal science / Charles Sorel -- The God that exists / Jean-Baptiste Morin
Includes bibliographical references (pages 261-264) and index
Keywords: Descartes, René, -- 1596-1650.; First philosophy; Metaphysics; Philosophy, Modern -- 17th century -- Sources; Philosophy, Modern -- 17th century -- Sources; Sources